Inequalities in Retention and Academic Performance in Virtual Environments: A Comparative Analysis Between Immigrant and Ecuadorian Students in Ecuador Participating in a Continuing Education Course in Moodle - Villarreal-Puga, Marcos; Villarreal Puga, Josué (REMHU, Revista Interdisciplinar da Mobilidade Humana, 2025)
This study examines inequalities in persistence and academic performance between foreign migrant and Ecuadorian students enrolled in a university continuing education course delivered virtually in Ecuador, aimed at both youth and adults. Based on automated records from the Moodle platform and institutional data, a quantitative, comparative, and multivariate approach was applied. The results reveal a significantly higher dropout rate among migrant students (over 40%), despite the fact that those who complete the course achieve levels of performance and participation equivalent to their Ecuadorian peers. In addition, migrant students were found to make more intensive use of supplementary materials, which may reflect compensatory strategies. The logistic regression model demonstrated a high predictive capacity for academic dropout (AUC = 0.949)...